Physiologically induced changes in bound phenolics and antioxidants, DNA/cytoprotective potentials in pectic poly/oligosaccharides of tomato (Solanum lycopersicum). (13th April 2016) - Kapoor, Sabeeta; Dharmesh, Shylaja M
Abstract: BACKGROUND: Antioxidant, cyto/DNA protective potentials are known to offer significant protection against free radical induced injury to cells or tissues and cellular damages that are envisaged in various diseases including chronic diseases like cancer, diabetes, etc, while galectin‐3 inhibitory potentials are known to block or delay the process of metastasis in cancer. Antioxidant, cyto/DNA protection and galectin‐3 inhibitory potentials were examined in pectic polysaccharides (PPs) and pectic oligosaccharides (POs) from four types of two varieties of tomatoes such as Sour (Mallika local variety) raw (SrRT–SrRTPP, SrRTPO), Sour ripe (SrRIT–SrRITPP, SrRITPO), Sweet (Rashmi local variety) raw (SwRT–SwRTPP, SwRTPO) and Sweet ripe (SwRIT–SwRITPP and SwRITPO). RESULTS: Results indicate that unripe PPs and POs show approximately four‐ to five‐fold better galectin‐3 inhibitory property than ripe ones. An approximately nine‐ to 10‐fold increase in galectin‐3 inhibitory activity in sour variety was observed. The IC50 as determined by free radical scavenging (FRS), red blood cell (RBC) and DNA protection assays revealed reduction in FRS and RBC protective potencies in pectic oligosaccharides (POs) than pectic polysaccharides (PPs), supporting the fact that phenolics contribute towards these activities. Loss of activity could be attributed to the hydrolysis of certain phenolics during the ripening process as well as during conversion of PPs to POs. CONCLUSION: This study, for the first time, showed changes in bioactivity profiling in unripened and ripened conditions in tomato. Precise alterations in biomolecular components, such as bound cinnamyl/ferulyl and vanillic acid derivatives, along with alterations in sugar composition that reflect changes in antioxidants, cyto/DNA protective and antimetastatic potentials, have been delineated. © 2016 Society of Chemical Industry